1971
DOI: 10.1111/j.1432-1033.1971.tb01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of the Binding of Various Glycolytic Enzymes to F‐Actin and the Interaction of Aldolase with G‐Actin

Abstract: The binding to F-actin of several crystalline rabbit muscle enzymes of glycogenolysis and glycolysis, was investigated in vitro. Under the conditions chosen, no binding occurs in the case of glycogen phosphorylase, phosphoglucomutase, glycerate phosphomutase and enolase. Aldolase, pyruvate kinase and triosephosphate dehydrogenase are strongly bound to F-actin, whereas lactate dehydrogenase and phosphoglycerate kinase are bound to a lesser degree. The quantitative differences in the affinity to F-actin are expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
49
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 24 publications
1
49
1
Order By: Relevance
“…A general effect of decreasing pH on increasing enzyme binding to actin was noted by Pette [6] for several enzymes other than aldolase. However, during the studies with perfused rat hearts we have not observed any marked increases in the binding of pyruvate kinase, lactate dehydrogenase or glyceraldehyde-3-phosphate dehydrogenase although such increases might have been expected on the basis of the known pH dependency of their absorption to actin filaments in vitro.…”
Section: Discussionmentioning
confidence: 76%
“…A general effect of decreasing pH on increasing enzyme binding to actin was noted by Pette [6] for several enzymes other than aldolase. However, during the studies with perfused rat hearts we have not observed any marked increases in the binding of pyruvate kinase, lactate dehydrogenase or glyceraldehyde-3-phosphate dehydrogenase although such increases might have been expected on the basis of the known pH dependency of their absorption to actin filaments in vitro.…”
Section: Discussionmentioning
confidence: 76%
“…The uniform distribution of Rh-aldolase we observed in vivo initally seemed paradoxical, in light of data demonstrating that aldolase hinds to F-actin (7,15,16), skeletal muscle homogenates (19), and fetal brain homogehates (17) with affinities greater than or equal to those of other glycolytic enzymes. However, the spatial differences we measured in the mobile fraction and diffusion coefficient of Rh-aldolase indicate that a sensitive equilibrium may regulate the actin-binding activity of aldolase in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports of the interactions of the enzyme with F-actin in vitro have been published since Arnold and Pette (1968) first suggested it. The dissociation constants (K d ) of the LDH-F-actin complex are very low, 8 nM (Poglazov and Livanova 1986) to 2.1 M (Arnold et al 1971). It is also known that purified LDH binds to intracellular proteins such as tubulin (K d ϭ 1.0 M), microtubules (K d ϭ 3.5 M) (Walsh et al 1989), and troponin (K d ϭ 0.73-2.3 M; Yasykova et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Previous histochemical studies, for example, have shown that muscle LDH, as well as other glycolytic enzymes, is predominantly localized within the isotropic zones of myofibrils (e.g., Dölken et al 1975, and references cited therein). Many biochemical studies have reported that some glycolytic enzymes, including LDH, interact with cytoskeletal proteins such as actin filaments (F-actin), tropomyosin, and troponin (e.g., Arnold and Pette 1968;Arnold et al 1971;Clarke et al 1985;Poglazov and Livanova 1986;Walsh and Knull 1987;Yasykova et al 1990), microtubules, and tubulin (Karkhoff-Schweizer and Knull 1987;Walsh et al 1989;Marmillot et al 1994). This evidence suggests that some glycolytic enzymes exist in both the fluid phase and the solid phase of the cytoplasm and that changes in the equilibrium between the two phases may play a role in the regulation of glycolytic metabolism within cells (Wilson 1978).…”
mentioning
confidence: 99%